New Plantations - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Zefoume Roger, Abong-Mbang, Cameroon: 'As an extension worker, and a grower of rubber and oil palm, I am looking forNGOs and other partners who can help me develop large-scale cultivation.' Spore: We suggest you contact the Support Service for Local...